2010
DOI: 10.1007/s11936-010-0088-3
|View full text |Cite
|
Sign up to set email alerts
|

Driving Guidelines and Restrictions in Patients With a History of Cardiac Arrhythmias, Syncope,or Implantable Devices

Abstract: The need to drive is universal in many countries. Patients with syncope, cardiac arrhythmias, or implantable cardioverter-defibrillators (ICDs) have an ongoing risk of sudden incapacitation that may cause harm to themselves and/or others when driving. Restrictions on driving and driving guidelines have been developed with the intent to reduce and prevent motor vehicle accidents, thereby improving personal and public safety. Several guidelines and consensus statements recently were updated. This review focuses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Implantable cardioverter defibrillators (ICDs) improve survival in patients at risk of sudden cardiac death [ 1 ]. However, these patients have an ongoing risk of sudden incapacitation that may cause harm to themselves and others when driving [ 2 – 10 ]. An obvious concern is the effect of arrhythmias and/or discharges of devices on a patient’s level of consciousness and ability to drive.…”
Section: Introductionmentioning
confidence: 99%
“…Implantable cardioverter defibrillators (ICDs) improve survival in patients at risk of sudden cardiac death [ 1 ]. However, these patients have an ongoing risk of sudden incapacitation that may cause harm to themselves and others when driving [ 2 – 10 ]. An obvious concern is the effect of arrhythmias and/or discharges of devices on a patient’s level of consciousness and ability to drive.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the clinical approach to syncope evaluation, and the recommendations for driving, should not differ with regard to the time or activity related to the presentation of the syncopal episode [14] . Several mechanisms or factors may trigger reflex syncope while driving: the passively seated position without muscle tension (enhances venous pooling in the legs), preexisting dehydration or intravascular depletion, the warm environment of a car (leads to cutaneous vasodilatation), and strong emotional stimulation while driving [1] , [14] , [15] , [16] .…”
Section: Recommendations To Prevent Syncope While Drivingmentioning
confidence: 99%
“…The benefits of pharmacological treatment such as beta-blockers, alpha-antagonists, and mineral corticoids have not been confirmed in long-term placebo-controlled trials, but these agents have shown some benefit in shorter-duration trials [16] . Non-pharmacological treatments such as counter-pressure maneuvers (including leg crossing, hand gripping, and arm tensing) could increase blood pressure significantly enough to delay or avoid loss of consciousness [16] , although it may be difficult to perform such a maneuver during driving. However, these recommendations are speculative and based on common sense, and there is insufficient evidence to support them at present [1] .…”
Section: Recommendations To Prevent Syncope While Drivingmentioning
confidence: 99%
See 2 more Smart Citations